EXPLORATION OF MEDICINAL PHYTO-DIVERSITY OF THE SEMI-ARID AREA IN PUNJAB PROVINCE, PAKISTAN - M. A. Akram; 2; N. Iqbal; M. Aqeel; N. Khalid; S. Alamri; M. Hashem; M. Abrar; A. Manan; W. Islam; A. Noman2 (Journal of Animal and Plant Sciences, 2020)
This is the first ethno-botanical study about the indigenous plants of district Faisalabad, Punjab-Pakistan. Main theme behind this study documents the existing ethno-medicinal data about local traditional herbal treatments. Overall, 300 local informants were interviewed from 22different locations of the district and collected data was analyzed by using different quantitative ethnobotanical tools. The 61 plants of 53 genera and 29 families be there found in use for 15 disease caused by microorganisms and contagious ones also. With reference to highest Use Value (UV), Ficus carica (0.83), Albizzia lebbeck (0.73) and Psidium guajava (0.71) were found the most used medicinal plant species in area. The 100% Fidelity Level (FL) was calculated for Acacia nilotica being used against gastro, respiratory, diabetics and hypertension. The highest Relative Frequency Citation (RFC) value was calculated for Citrus aurantifolia. The maximum Informant Consensus Factor (ICF) index was calculated for gastro and respiratory problems, fever, headache, and skin infection. The comparative study by calculating Jaccard Index (JI) with reported literature was shown that 8.18%resemblance and 12.81% distinction to earlier studies; however 79.01% medicinal uses of the reported species were documented the first time. The plants reported with high RPL index can be further analyzed for biochemical pharmaceutical and biotechnological screening.
Keywords: Biochemical; Diseases; Ethnobotanical study; Jaccard Index; Popular